Is there a link between immigration and incarceration rate?: Evidence from the Syrian refugee influx to Turkey - Mercan, Murat A.; Barlin, Hande; Begen, Nazire (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
In this study, we investigate the impact of an increase in the number of refugees on a host country's incarceration rate, through the specific case of the inflow of Syrian refugees into Turkey. Using statistics from Turkish penal institutions for the period of 2010 to 2015, we applied the difference-in-difference, panel event study, synthetic control, and instrumental variable approaches to measure the changes in the incarceration rate during the time of peak Syrian refugee migration. Our results suggest that the refugee influx into sampled Turkish cities did not have a statistically significant impact on the incarceration rate when compared to control locations. All four of the methods yielded similar results in the robustness exercises designed to check the relationship between the number of refugees and the rate of incarceration.
Keywords: Refugees; immigrants; incarceration rates; natural experiment; QUASI-EXPERIMENTAL EVIDENCE; CRIME RATES; IMPACT; ASSIMILATION; CONFLICT; VIOLENCE; EXPLAIN; Criminology & Penology